Clinical reasoning for complex cervical spine conditions. (March 2018) - Reid, Duncan; Rebbeck, Trudy; McCarthy, Christopher
Abstract: Clinical reasoning is at the cornerstone of clinical practice. Case studies are not viewed as highly in the evidence hierarchy as randomised controlled trials but they provide valuable insights into individual cases and clinicians often relate well to these as there are parallels with patients they see in their own clinics. This master class presents three cases related to cervical spine pathologies as assessed or managed by three physiotherapists. These therapist are experienced clinicians and academics and bring their expertise of both worlds (clinical and academic) to these cases providing an overview of the case, followed by their interpretation and rationale for care with their clinical reasoning insights. The cases where originally presented at a recent international physiotherapy conference and reworked for journal publication.